PERANCANGAN SISTEM PEMANTAUAN WAKTU NYATA BERBASIS INTERNET of THINGS (IoT) - Mat Sudir; Bambang Soedjono W A; Eko Pramono (Informasi Interaktif, 2019)
Physically, humans can feel heat and or hot through sensory sense events and can be categorized as qualitative data. However, quantitatively, there will be need data that can be processed and displayed visually as a basis for interpretation in a system. In this study will be designed a connection simulation from remote monitoring by microcontroller. Monitoring system in real time based on Internet of Things (IoT) will monitor physical phenomena in the form of temperature and humidity in space. Data will be processed for revisualization. Then the difference value of each measurement is calculated (in the same time identity). This difference value will be used to calculated the level of shift in site information ( the acquisition of  NodeMCU ) with  local measurements ( the results of the acquistion). The Internet of Things (IoT) based system is a system that utilizes internet technology as a forum for information distribution. The use of microcontrollers has been widely applied to activities that cover the general activities of the community. Ranging from building automation to making smart buildings. The simulation of the connection flow will be examined further in the evaluation system that will be built later. Keywords: Fenomena, IoT, Mikrokontroler, Monitoring